Peranan Akuntansi Sektor Publik Terhadap Efektivitas Pengelolaan Pendapatan dan Biaya Pada Enhaii Hotel Bandung - Choirudin, Nor Ismawanto (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
The development of hospitality services is growing rapidly, along with the marry role of investor in the development of the service is no exception to the government, the mechanism of the implementation of hotel financial management in addition managed by the private sector is also managed by the public or government sectors, but the nature and characteristics are different. The purpose of public sector organizations is motivated nonprofit while the private sector is profitable. Sources of public sector financing are derived from taxes, corporate profits of SOEs / SOEs, etc. while private sector financing comes from owner's capital, retained earnings, bank loans, and so on. The pattern of public sector responsibility to the public and the parliament while the private sector is accountable to shareholders, owners and creditors. The organizational structure of the public sector is bureaucratic, rigid and hierarchical while the private sector is flexible. Characteristics of the public sector budget are open to the public while the private sector is closed to the public. Accounting system used public sector cash accounting while private sector accrual accounting. Based on the above, the purpose of this study is to find out how: (1) implementation of public sector accounting role in Enhaii Hotel; (2) implementation of revenue and cost management effectiveness at Enhaii Hotel; and (3) role of public sector accounting on effectiveness Revenue management and fees at Enhaii Hotel. The research methodology applied is qualitative research method with case study at Enhaii Hotel Bandung, data collecting technique is done by observation, interview, document and bibliography, while the model of analysis used is Miles and Huberman model that is data reduction, data display, and data verification. The results of the discussion show that the role of public sector accounting on the effectiveness of revenue and cost management is still less than optimal, this is because it is limited by binding rules, the arrangement of types and sales tariff has been regulated by the government so that income must be deposited to the state treasury as Non-Tax State Revenues (PNBP) And the use of operational costs based on the government budget listed in the List of Budget Implementation (DIPA) STP Bandung because Enhaii Hotel is part of the STP Bandung unit.